2010
DOI: 10.2217/nnm.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Chemorad Nanoparticles: A Novel Multifunctional Nanoparticle Platform for Targeted Delivery of Concurrent Chemoradiation

Abstract: Aim-The development of chemoradiation -the concurrent administration of chemotherapy and radiotherapy -has led to significant improvements in local tumor control and survival. However, it is limited by its high toxicity. In this study, we report the development of a novel NP (nanoparticle) therapeutic, ChemoRad NP, which can deliver biologically targeted chemoradiation.Method-A biodegradable and biocompatible lipid-polymer hybrid NP that is capable of delivering both chemotherapy and radiotherapy was formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 22 publications
0
62
0
Order By: Relevance
“…16 These LPNPs have exhibited some unique advantages of both liposomes and polymeric nanoparticles, including high structural integrity, stability during storage, controlled release capability, high biocompatibility, and favorable pharmacokinetic profile, while excluding some of their intrinsic limitations. 13,14,17,18 LPNPs are usually prepared through a single-step nanoprecipitation method 12,[19][20][21] or a two-step method involving co-incubation of separately preformed nanoparticles and lipid vesicles (or lipid films). [22][23][24] The hydrophobic polymeric core of the LPNPs are commonly made of polylacticco-glycolic acid (PLGA), poly(ε-caprolactone) (PCL), dextran, or albumin because of their biocompatibility, biodegradability, nontoxicity, and previous use in approved products.…”
Section: Introductionmentioning
confidence: 99%
“…16 These LPNPs have exhibited some unique advantages of both liposomes and polymeric nanoparticles, including high structural integrity, stability during storage, controlled release capability, high biocompatibility, and favorable pharmacokinetic profile, while excluding some of their intrinsic limitations. 13,14,17,18 LPNPs are usually prepared through a single-step nanoprecipitation method 12,[19][20][21] or a two-step method involving co-incubation of separately preformed nanoparticles and lipid vesicles (or lipid films). [22][23][24] The hydrophobic polymeric core of the LPNPs are commonly made of polylacticco-glycolic acid (PLGA), poly(ε-caprolactone) (PCL), dextran, or albumin because of their biocompatibility, biodegradability, nontoxicity, and previous use in approved products.…”
Section: Introductionmentioning
confidence: 99%
“…12 Wang et al developed a lipid-polymer hybrid NP for prostate cancer that is capable of delivering both chemotherapy and radiotherapy. 13 These nanoparticles can encapsulate chemotherapeutics up to 9% of the nanoparticle weight and radiotherapeutics of 100 mCi of radioisotope per gram. 13 Cisplatin (CDDP)-loaded magnetic nanoparticles (MNP) in combination with chemoradiotherapy showed that CDDP-loaded MNP alone or in combination with radiotherapy can effectively inhibit the growth of nasopharyngeal carcinoma in nude mice without increasing the toxicity.…”
mentioning
confidence: 99%
“…13 These nanoparticles can encapsulate chemotherapeutics up to 9% of the nanoparticle weight and radiotherapeutics of 100 mCi of radioisotope per gram. 13 Cisplatin (CDDP)-loaded magnetic nanoparticles (MNP) in combination with chemoradiotherapy showed that CDDP-loaded MNP alone or in combination with radiotherapy can effectively inhibit the growth of nasopharyngeal carcinoma in nude mice without increasing the toxicity. 14 Ho emits 81-keV γ-rays (6.6% photon yield), which can be used to quantify and image the biodistribution of the particles.…”
mentioning
confidence: 99%
“…Amphiphilic character of lipids facilitates the adsorption of hydrophilic compounds on the hydrophilic bilayer surface and insertion of hydrophobic molecules into the hydrophobic lamellar region (129)(130)(131)(132). This feature allows CSLPHNPs to entrap and deliver multiple hydrophilic and hydrophobic therapeutic agents simultaneously into the single delivery platform (99,133).Optimization of the core and shell properties can result in tunable and sustained drug release profiles (134). CSLPHNPs exhibit storage and serum stability over prolonged periods (104,134).…”
Section: Advantages Of Cslphnpsmentioning
confidence: 99%
“…This feature allows CSLPHNPs to entrap and deliver multiple hydrophilic and hydrophobic therapeutic agents simultaneously into the single delivery platform (99,133).Optimization of the core and shell properties can result in tunable and sustained drug release profiles (134). CSLPHNPs exhibit storage and serum stability over prolonged periods (104,134). Besides passive targeting of CSLPHNPs based on particle size, they can be conjugated with appropriate targeting ligands such as aptamers (134), folic acid (97,135), transferrin (136), anticarcinoembryonic antigen half-antibody (94), single-chain tumor necrosis factor (121) to deliver NPs at the target tissues for treating cancers.…”
Section: Advantages Of Cslphnpsmentioning
confidence: 99%